Experience with cyclophosphamide in the treatment of a young woman with refractory dermatomyositis - Bambang Setiyohadi; R Sinto (Indonesian Rheumatology Association, 2011)
Dermatomyositis is an idiopathic inflammatory myopathy characterized by the presence of rash and moderate-to-severe muscle weakness secondary to inflammation of the muscle. It can be a difficult condition to treat. Systemic corticosteroids are the first choice of treatment. However, about a quarter of patients either fail to respond to steroids or develop steroid-related toxicity. Second-line agents such as azathioprine and methotrexate are then added either alone, or in combination with corticosteroids. Failure of the disease to respond tosecond-line agents can then be a problem and this is often referred to as â€œrefractory dermatomyositisâ€. Unfortunately, there is neither agreement nor wellestablished guidelines on the best regimen or combination of immunosuppressive agents in the case of refractory dermatomyositis.